Polymer particles and polymer particle composition for producing three-dimensional shaped article, method for producing polymer particles, and

By using polymer particles and polymer particle compositions with high spherical and specific compositions, the problem of particle surface deterioration during reuse of molding in powder bed fusion method is solved, and the surface smoothness and mechanical strength of molding are maintained. , improves the recovery of residual particles.

CN119212848APending Publication Date: 2024-12-27TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380041336.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-31
Filing Date
2023-08-03
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In powder bed fusion method, when reusing the molding using a large molding machine with a long molding time, the particle surface of the polymer particles is prone to deterioration, resulting in changes in the characteristics of the molding and making it difficult to maintain surface smoothness and mechanical strength.

Method used

Polymer particles and polymer particle compositions with high spheres, small ratio of terminal carboxyl groups to terminal amino groups of polyamides and few impurities are used to ensure high spheres of polymer particles through specific heating treatment and composition design. and appropriate end adjuster content, polyamide 12, polyamide 11, polyamide 1012, polyamide 1010, polyamide 6, polyamide 66, etc. are used as the matrix of the polymer, and flow additives and inorganic reinforcement materials are added.

Benefits of technology

When reusing the molding in large molding machines, the surface smoothness and mechanical strength of the molding can be maintained, the recovery of residual particles can be improved, the waste particles can be reduced, and the stability and performance of the molding can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212848A_ABST
    Figure CN119212848A_ABST
Patent Text Reader

Abstract

Polymer particles for producing a three-dimensionally shaped article, which are used for producing a three-dimensionally shaped article by a powder bed fusion method and comprise a polyamide, the sphericity of the polymer particles being 80 or more, the average particle diameter of the polymer particles being 1 [mu] m to 100 [mu] m, and the average particle diameter of the polymer particles being 1 [mu] m or more and 100 [mu] m or less. The ratio of the amount of terminal carboxyl groups to the amount of terminal amino groups in the polyamide constituting the polymer particles is 0.01-0.8, and the content of the terminal regulator in the polymer particles is more than 0 wt% and 0.2 wt% or less. According to the present invention, by using polymer particles in which the ratio of the amount of terminal carboxyl groups to the amount of terminal amino groups in polyamide is small and the amount of impurities is small, the surface smoothness and mechanical strength of a molded article can be maintained without mixing a large amount of new polymer particles when reusing and molding a three-dimensional molded article using a large molding machine, and the remaining particles can be easily recovered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to polymer particles and polymer particle compositions suitable for manufacturing three-dimensional objects by powder bed fusion bonding, a method for manufacturing polymer particles, and three-dimensional objects and a method for manufacturing the same. In particular, it relates to polymer particles and polymer particle compositions suitable for recovering polymer particles and polymer particle compositions that remain after molding without forming an object and using them for molding again. Background Art

[0002] As a technology for manufacturing three-dimensional shaped articles (hereinafter sometimes referred to as articles), a powder bed fusion method is known. The article obtained by the powder bed fusion method is manufactured by repeating the following steps in sequence: a thin layer forming step of unfolding the powder into a thin layer, and a cross-sectional shape forming step of selectively melting the formed thin layer into a shape corresponding to the cross-sectional shape of the article to combine the resin powder particles. Here, as a method for selectively melting the powder, in addition to the selective laser sintering method of selectively irradiating a laser at a position corresponding to the cross-sectional shape of the article after setting the powder layer, there is also a selective absorption sintering method or a selective inhibition sintering method of irradiating a laser or other energy rays after printing an absorber or inhibitor of electromagnetic radiation at a position corresponding to the cross-sectional shape of the article. This method can achieve high dimensional accuracy and mechanical strength of the article, so it is expected to expand rapidly.

[0003] In the powder bed fusion method, most of the powder used is not a molded object, but is recovered as residual polymer particles. In order to reduce waste particles, it is preferred to reuse the residual particles for molding (hereinafter sometimes referred to as reused molding). However, the residual particles are exposed to a temperature slightly below the melting point during molding, so that the molecular weight of the polymer increases. Therefore, the properties of the molded object obtained by recycling molding are different from those of the molded object obtained by using new powder molding. In order to maintain the properties of the molded object and reuse the molding, it is necessary to mix a large amount of new particles into the residual particles and discard the residual powder according to the amount of new powder added.

[0004] To address such a problem, a polyamide powder having an excess of carboxyl terminal groups is disclosed in Patent Document 1. A polyamide powder having a solution viscosity that is suppressed from increasing due to heating is disclosed in Patent Document 2.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2004-137465

[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-59093 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, in the techniques described in Patent Documents 1 and 2, although the increase in molecular weight during molding can be suppressed, the particle surface is easily degraded during molding because the particle shape is amorphous. Therefore, the problem of easy change in the properties of the molded object occurs, especially when a large-scale molding machine with a long molding time is used for recycling molding.

[0011] Therefore, the subject of the present invention is to maintain the surface smoothness and mechanical strength of the molded object even without mixing a large amount of new polymer particles and polymer particle compositions when recycling the molded object using a large-scale molding machine with a long molding time, thereby making the recyclability of the residual particles excellent by using polymer particles and polymer particle compositions with high sphericity, a small ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide constituting the particles, and a small amount of impurities.

[0012] Solution

[0013] In order to solve the above problems, the present invention has the following solutions.

[0014] [1]. A polymer particle for manufacturing a three-dimensional object, which is a polymer particle composed of polyamide and is used to manufacture a three-dimensional object by a powder bed fusion method, wherein the sphericity of the polymer particles is greater than 80, the average particle size of the polymer particles is greater than 1 μm and less than 100 μm, the ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide constituting the polymer particles is greater than 0.01 and less than 0.8, and the content of the terminal regulator in the polymer particles is greater than 0 weight % and less than 0.2 weight %.

[0015] [2] The polymer particles for producing three-dimensional objects as described in [1], wherein when the polymer particles are heated at a temperature of -5°C, the melting point of the polyamide constituting the polymer particles, for 12 hours in a nitrogen atmosphere, the molecular weight change rate of the polyamide constituting the polymer particles before and after heating is greater than 0.7 and less than 1.4.

[0016] [3] The polymer particles for producing three-dimensional objects as described in [1] or [2], wherein the weight average molecular weight of the polyamide constituting the polymer particles is greater than or equal to 1000 g / mol and less than or equal to 100000 g / mol.

[0017] [4] The polymer particles for producing a three-dimensional object according to any one of [1] to [3], wherein the amount of terminal amino groups of the polyamide constituting the polymer particles is 0.1×10 -5 mol / g or more and 4.0×10 -5 mol / g or less.

[0018] [5] The polymer particles for producing three-dimensional objects according to any one of [1] to [4], wherein the BET specific surface area of ​​the polymer particles is 0.05 m 2 / g or more and 1m 2 / g or less.

[0019] [6] The polymer particles for manufacturing three-dimensional objects as described in any one of [1] to [5], wherein the polyamide constituting the polymer particles comprises at least one polyamide selected from polyamide 12, polyamide 11, polyamide 1012, polyamide 1010, polyamide 6, polyamide 66 and copolymers containing any of these polyamides.

[0020] [7] A polymer particle composition for producing a three-dimensional object, comprising 0.01 parts by mass or more and 5 parts by mass or less of a flow aid per 100 parts by mass of the polymer particles described in any one of [1] to [6].

[0021] [8] A polymer particle composition for producing a three-dimensional object, comprising 10 parts by mass or more and 200 parts by mass or less of an inorganic reinforcing material per 100 parts by mass of the polymer particles described in any one of [1] to [6].

[0022] [9] A method for producing a three-dimensional object, comprising using the polymer particles described in any one of [1] to [6] to produce the three-dimensional object by a powder bed fusion method.

[0023]

[10] A method for producing a three-dimensional object, comprising using the polymer particle composition described in [7] or [8] to produce the three-dimensional object by powder bed fusion.

[0024]

[11] . A three-dimensional object obtained by powder bed fusion using polymer particles or a polymer particle composition, characterized in that the three-dimensional object contains a surface with a surface roughness of less than 15 μm, the average equivalent spherical diameter of the pores observed by X-ray CT measurement is greater than 1 μm and less than 100 μm, the ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide constituting the three-dimensional object is greater than 0.01 and less than 0.8, and the terminal regulator content is greater than 0 weight % and less than 0.15 weight %.

[0025]

[12] . The method for producing polymer particles for producing three-dimensional objects described in [1] is a method for producing polymer particles by polymerizing a polyamide monomer (a) in the presence of a polymer (B) and a terminal regulator (C), characterized in that at the beginning of polymerization, the polyamide monomer (a) is uniformly dissolved in the polymer (B), and after polymerization, polymer particles (A) are precipitated, and the solubility parameters δ of the polyamide, polymer (B), and terminal regulator (C) constituting the polymer particles (A) are A , δ B , δ C Satisfy 2≤(δ B -δ C ) 2 -(δ A -δ C ) 2 ≤50[(J / cm 3 )], the amount of the terminal regulator (C) is 0.001 mol% or more and 4.0 mol% or less.

[0026] Effects of the Invention

[0027] According to the present invention, when polymer particles or polymer particle compositions having high sphericity, a small ratio of the amount of terminal carboxyl groups to the amount of terminal amino groups of the polyamide constituting the polymer particles, and a small amount of impurities are used, the surface smoothness and mechanical strength of the molded object can be maintained even without mixing a large amount of new polymer particles or polymer particle compositions, and the residual particles can be easily recovered. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram showing an example of the manufacturing apparatus of the three-dimensional modeled object of the present invention. DETAILED DESCRIPTION

[0029] Hereinafter, the present invention will be described in detail together with embodiments.

[0030] The polymer particles of the present invention are polymer particles composed of polyamide used to manufacture three-dimensional objects by powder bed fusion. The sphericity of the polymer particles is greater than 80, the average particle size of the polymer particles is greater than 1 μm and less than 100 μm, the ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide constituting the polymer particles is greater than 0.01 and less than 0.8, and the terminal regulator content of the polymer particles is greater than 0 weight % and less than 0.2 weight %. The polymer particles are polymer particles used to manufacture three-dimensional objects.

[0031] The sphericity of the sphericity of the polymer particles of the present invention is more than 80. If the sphericity is high, the surface area tapers, and the degradation of the polymer particles during the molding can be suppressed. When the large molding machine is reused for molding, even if new polymer particles and polymer particle compositions are not mixed in a large amount, the surface smoothness and mechanical strength of the molding object can be maintained. The sphericity is preferably more than 85, more preferably more than 90, further preferably more than 92, and particularly preferably more than 95. In addition, its upper limit is 100 in theory.

[0032] The sphericity of the polymer particles of the present invention is calculated by observing 30 particles at random from a scanning electron microscope photograph and calculating the average value of the ratio of the minor axis to the major axis of each particle as shown in the following formula.

[0033]

[0034] In the above formula, S represents sphericity, a represents the major axis, b represents the minor axis, and n represents the number of measurements, which is 30.

[0035] The average particle size of the polymer particles of the present invention is in the range of 1 μm to 100 μm. The smaller the average particle size, the better the surface smoothness of the molded object. The upper limit of the average particle size of the polymer particles is preferably 90 μm or less, more preferably 80 μm or less, and further preferably 75 μm or less. If the average particle size is too small, the particles are easily aggregated due to their fineness, and the surface smoothness may be deteriorated. The lower limit is more preferably 5 μm or more, more preferably 20 μm or more, and particularly preferably 30 μm or more.

[0036] The average particle size of the polymer particles of the present invention refers to the D50 particle size. The D50 particle size of the polymer particles is measured by a laser diffraction particle size distribution measuring device. In addition, the D50 particle size of the polymer particles refers to the particle size when the cumulative distribution of the particle size distribution measured by the laser diffraction particle size distribution measuring device from the small particle size side reaches 50%.

[0037] The ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide constituting the polymer particles of the present invention is 0.01 or more and 0.8 or less. When the ratio of the terminal carboxyl group amount to the terminal amino group amount is small, the molecular weight change during molding can be suppressed, and when the molding is reused in a large molding machine, even if a large amount of new polymer particles and polymer particle compositions are not mixed, the mechanical strength of the molded object can be maintained. The upper limit of the ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide is preferably 0.6 or less, more preferably 0.4 or less, and further preferably 0.2 or less. In addition, if the ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide is too close to 0, the mechanical strength of the obtained molded object becomes low, so the lower limit is preferably 0.05 or more, more preferably 0.1 or more.

[0038] The ratio of the terminal carboxyl amount and the terminal amino amount of the polyamide constituting the polymer particles refers to the value obtained by dividing the small functional group amount by the large functional group amount in the terminal carboxyl amount and the terminal amino amount. In addition, the terminal amino of the polyamide constituting the polymer particles is easily oxidized compared with the terminal carboxyl. Therefore, the terminal amino amount of the polyamide constituting the polymer particles is preferably less than the terminal carboxyl amount. The theoretical upper limit of the ratio of the terminal carboxyl amount and the terminal amino amount is 1, and the lower limit is 0.

[0039] The terminal carboxyl group content of the polyamide was determined by dissolving the polymer particles in benzyl alcohol and then neutralizing and titrating with a potassium hydroxide ethanol solution, and the terminal amino group content of the polyamide was determined by dissolving the polymer particles in PEA (phenol-ethanol solvent) and then neutralizing and titrating with a hydrochloric acid aqueous solution.

[0040] The terminal carboxyl group content and the terminal amino group content of the polyamide are preferably 0.1×10 -5 mol / g or more and 20×10 - 5 mol / g or less. The smaller the amount of terminal carboxyl groups and terminal amino groups, the more the molecular weight change during molding can be suppressed. When the molding is reused in a large molding machine, the mechanical strength of the molded object can be maintained even if a large amount of new polymer particles and polymer particle compositions are not mixed. The upper limits of the amount of terminal carboxyl groups and the amount of terminal amino groups are more preferably 5.0×10 -5 mol / g or less, more preferably 4.0×10 -5 mol / g or less, particularly preferably 3.0×10 -5 mol / g or less, particularly preferably 2.0×10 -5 On the other hand, if the amount of terminal carboxyl groups and the amount of terminal amino groups are too small, the mechanical strength of the obtained shaped object will be reduced. Therefore, the lower limits of the amount of terminal carboxyl groups and the amount of terminal amino groups are more preferably 0.5×10 -5 mol / g or more, more preferably 0.8×10 - 5 mol / g or above.

[0041] The terminal regulating agent content of the polymer particles in the present invention refers to the weight percentage concentration of the terminal regulating agent contained in the polyamide constituting the polymer particles and remaining without reacting with the polyamide.

[0042] The terminal regulator in the present invention refers to a compound that can react with a terminal amino group or a terminal carboxyl group of a polyamide to adjust the amount of the terminal amino group or the amount of the terminal carboxyl group of the polyamide.

[0043] The terminal regulator is defined differently depending on the type of polyamide monomer constituting the polymer particles. When dicarboxylic acids or diamines are used as polyamide monomers, monofunctional compounds are defined as terminal regulators, and when amino acids or lactams are used as polyamide monomers, in addition to monofunctional compounds, bifunctional compounds are also defined as terminal regulators.

[0044] As monofunctional terminal regulators, monoamines or monocarboxylic acids can be cited. Specific examples of monoamines include hexylamine, octylamine, dodecylamine, hexadecylamine, octadecylamine, aniline, aniline derivatives, benzylamine, phenylethylamine, etc. Specific examples of monocarboxylic acids include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, lactic acid, malic acid, citric acid, benzoic acid, benzoic acid derivatives, etc. As bifunctional terminal regulators, diamines or dicarboxylic acids can be cited. Specific examples of diamines include hexamethylenediamine, nonamethylenediamine, decanediamine, undecanediamine, dodecanediamine, and phenylenediamines, and specific examples of dicarboxylic acids include adipic acid, azelaic acid, sebacic acid, undecanediamine, dodecanediamine, terephthalic acid, and isophthalic acid. From the viewpoint of suppressing agglomeration during particle formation, monocarboxylic acids as monofunctional terminal regulators are more preferred, and from the viewpoint of suppressing the disappearance of monocarboxylic acids even at high temperatures during polymerization, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, citric acid, benzoic acid, and benzoic acid derivatives are particularly preferred.

[0045] The terminal regulating agent content of the polymer particles is calculated by adding the polymer particles to a solvent that does not dissolve the polymer particles but only dissolves the terminal regulating agent, stirring the mixture, and measuring the weight of the terminal regulating agent extracted into the solvent.

[0046] In the present invention, the content of the terminal regulator is greater than 0% by weight and is less than 0.2% by weight. The less the content of the terminal regulator, the easier it is to recover the residual particles after molding. The upper limit is more preferably less than 0.15% by weight, more preferably less than 0.1% by weight, particularly preferably less than 0.05% by weight, and particularly preferably less than 0.02% by weight. The lower limit is more than 0% by weight, but is preferably more than 0.00001% by weight, and more preferably more than 0.0001% by weight.

[0047] When the polymer particles of the present invention are heated for 12 hours under a nitrogen atmosphere at a temperature of -5°C, the melting point of the polyamide constituting the polymer particles, the molecular weight change rate of the polyamide constituting the polymer particles before and after heating (hereinafter sometimes referred to as the molecular weight change rate) is preferably 0.7 or more and 1.4 or less. If the molecular weight change rate is close to 1, the molecular weight change during molding can be suppressed, and when the molding is reused in a large molding machine, the mechanical strength of the molded object can be maintained even if a large amount of new polymer particles and polymer particle compositions are not mixed. The upper limit of the molecular weight change rate is more preferably less than 1.2, and more preferably less than 1.1. The lower limit of the molecular weight change rate is more preferably more than 0.8, and more preferably more than 0.9.

[0048] The molecular weight change rate refers to a value obtained by dividing the weight average molecular weight of the polyamide constituting the polymer particles in the polymer particles obtained by heating 5 g of the polymer particles at a temperature of -5°C, the melting point of the polyamide constituting the polymer particles, for 12 hours under a nitrogen atmosphere by the weight average molecular weight of the polyamide constituting the polymer particles before heating.

[0049] The melting point of the polyamide constituting the polymer particles of the present invention is the peak value of an endothermic peak observed by DSC method when heating from 30°C at a rate of 20°C / min in a nitrogen atmosphere to a temperature 30°C higher than the end point of the melting peak.

[0050] The weight average molecular weight of the polyamide constituting the polymer particles of the present invention refers to a weight average molecular weight obtained by converting a value measured by gel permeation chromatography using hexafluoroisopropanol as a solvent into polymethyl methacrylate.

[0051] The weight average molecular weight of the polyamide constituting the polymer particles of the present invention is preferably 1000 g / mol or more and 100000 g / mol or less. The smaller the weight average molecular weight, the lower the melt viscosity and the higher the mechanical strength. The upper limit of the weight average molecular weight is more preferably 90000 or less, further preferably 80000 or less, particularly preferably 70000 or less, and particularly preferably 60000 or less. When the weight average molecular weight is too small, the original characteristics of the polymer cannot be manifested, and the mechanical strength is reduced. The lower limit of the weight average molecular weight is more preferably 10000 or more, and more preferably 20000 or more.

[0052] The BET specific surface area of ​​the polymer particles of the present invention is preferably 0.05 m 2 / g above 1m 2 If the BET specific surface area is small, the particle surface is less likely to deteriorate during molding, and when the molding is reused in a large molding machine, the surface smoothness and mechanical strength of the molded object can be maintained even if a large amount of new polymer particles and polymer particle compositions are not mixed. The upper limit of the BET specific surface area is more preferably 0.9 m 2 / g or less, more preferably 0.8m 2 / g or less, particularly preferably 0.7m 2 / g or less, particularly preferably 0.6m 2 Theoretically, the lower limit of the BET specific surface area depends on the particle size and is 0.05 m when the particle size is 100 μm. 2 / g, 0.1m at 50μm 2 / g. Therefore, when the BET specific surface area is small, the particle size becomes larger, and the surface smoothness of the molded object becomes worse. Therefore, the lower limit of the BET specific surface area is more preferably 0.07 m 2 / g or more, more preferably 0.09m 2 / g or above.

[0053] The BET specific surface area is measured in accordance with Japanese Industrial Standards (JIS Standards) JIS R1626 (1996) "Method for measuring specific surface area by gas adsorption BET method".

[0054] The polymer particles in the present invention are composed of polyamides having an amide group-containing structure. Specific examples of the polyamides include polycaprolactam (polyamide 6), polyhexamethylene adipamide (polyamide 66), polyhexamethylene terephthalamide (polyamide 6T), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene dodecane diamide (polyamide 612), polydecamethylene adipamide (polyamide 106), polydodecane diamide (polyamide 126), polyamide 4, polybutylene adipamide (polyamide 46), polybutylene sebacamide (polyamide 410), polypentamethylene adipamide (polyamide 56), poly Pentamethylenediamine sebacate (polyamide 510), polynonanamide (polyamide 9), polydecanediamine terephthalamide (polyamide 10T), polydecanediamine sebacate (polyamide 1010), polydecanediamine dodecane (polyamide 1012), polyundecanamide (polyamide 11), polylauramide (polyamide 12), polydodecanediamine dodecane (polyamide 1212), polydodecane terephthalamide (polyamide 12T), polycaprolactam / polyhexamethyleneadipamide copolymer (polyamide 6 / 66), or copolymers thereof, etc. Among them, from the viewpoint of heat resistance, polycaprolactam (polyamide 6), polyhexamethyleneadipamide (polyamide 66), polyhexamethyleneterephthalamide (polyamide 6T), polyhexamethylenediamine sebacate (polyamide 610) are more preferred, and polycaprolactam (polyamide 6) and polyhexamethyleneadipamide (polyamide 66) are particularly preferred.

[0055] The polyamide can be copolymerized within a range that does not impair the effects of the present invention. As the copolymerizable component, an elastomer component such as polyolefin or polyalkylene glycol that imparts flexibility, a rigid aromatic component that improves heat resistance or strength, and the like can be appropriately selected.

[0056] The polymer particles of the present invention may contain a flow aid, and may also be used for three-dimensional modeling in the form of a polymer particle composition containing a flow aid. Preferably, the flow aid is dry-mixed into the polymer particles. In the present invention, the flow aid refers to a substance that inhibits the aggregation of polymer particles through the adhesion between polymer particles. By containing a flow aid, the fluidity of the polymer particles can be improved, and the surface smoothness of the modeling object can be improved.

[0057] Examples of the flow aid include silicon oxide (silicon dioxide) such as fused silica, crystalline silica, and amorphous silica, aluminum oxide (aluminum oxide), alumina colloid (alumina sol), aluminum oxide such as alumina white, light calcium carbonate, heavy calcium carbonate, finely powdered calcium carbonate, calcium carbonate such as special calcium carbonate fillers, nepheline syenite fine powder, sintered clay such as montmorillonite and bentonite, clay (aluminum silicate powder) such as silane-modified clay, talc, diatomaceous earth, silica sand and other silicic acid-containing compounds, pumice powder, pumice balloons, slate, and the like. The present invention also includes pulverized products of natural minerals such as aluminum powder, mica powder, barium sulfate, lithopone, calcium sulfate, molybdenum disulfide, graphite and other minerals, glass fiber, glass beads, glass flakes, glass fillers such as foamed glass beads, fly ash balls, volcanic glass hollow bodies, synthetic inorganic hollow bodies, single crystal potassium titanate, carbon fiber, carbon nanotubes, carbon hollow spheres, fullerenes, anthracite powder, artificial cryolite (cryolite), titanium oxide, magnesium oxide, basic magnesium carbonate, dolomite, potassium titanate, calcium sulfite, mica, asbestos, calcium silicate, molybdenum sulfide, boron fiber, silicon carbide fiber, etc. More preferably, silicon dioxide, aluminum oxide, calcium carbonate powder, glass fillers, and titanium oxide are used. Silicon dioxide is particularly preferred.

[0058] Commercially available products of the silica include the fumed silica "AEROSIL" (registered trademark) series manufactured by Nippon Aerosil Co., Ltd., the dry silica "LEROSIUL" (registered trademark) series manufactured by Tokuyama Co., Ltd., and the sol-gel silica PAUDA X-24 series manufactured by Shin-Etsu Chemical Co., Ltd.

[0059] Relative to 100 parts by mass of polymer particles, the amount of the flow aid is preferably 0.01 parts by mass or more and 5 parts by mass or less. The upper limit of the amount is preferably 4 parts by mass or less, more preferably 3 parts by mass or less, further preferably 2 parts by mass or less, and particularly preferably 1 part by mass or less. In addition, the lower limit of the amount is preferably 0.02 parts by mass or more, more preferably 0.03 parts by mass or more, further preferably 0.05 parts by mass or more, and particularly preferably 0.1 parts by mass or more. When the amount of the flow aid is less than 0.01 parts by mass, the fluidity is insufficient and the effect of improving the surface smoothness cannot be shown. In addition, if the amount of the flow aid exceeds 5 parts by mass, it is possible that the flow aid covers the surface of the polymer particles and causes sintering hindrance and the molded object cannot be obtained.

[0060] The polymer particles of the present invention may contain an inorganic reinforcing material composed of an inorganic compound, or may be used for three-dimensional modeling in the form of a polymer particle composition containing an inorganic reinforcing material. The inorganic reinforcing material may be dry mixed with respect to the polymer particles, or may be contained inside the polymer particles, but dry mixing is preferably performed from the viewpoint of controlling the polymer particles to be spherical and improving fluidity.

[0061] Examples of the inorganic reinforcing material include glass fillers such as glass fibers, glass beads, glass flakes, and foamed glass beads, clays (aluminum silicate powders) such as fine powder of nepheline syenite, smectite, bentonite, and other calcined clays, and silane-modified clays, talc, diatomaceous earth, silica sand, and other compounds containing silica, crushed products of natural minerals such as pumice powder, pumice balloons, slate powder, and mica powder, minerals such as barium sulfate, lithopone, calcium sulfate, molybdenum disulfide, and graphite, silicon oxides (silicon dioxide) such as fused silica, crystalline silica, and amorphous silica, and aluminum oxides (aluminum trioxide). ), alumina colloid (alumina sol), alumina white and other alumina, light calcium carbonate, heavy calcium carbonate, finely powdered calcium carbonate, calcium carbonate such as special calcium carbonate fillers, fly ash balls, volcanic glass hollow bodies, synthetic inorganic hollow bodies, single crystal potassium titanate, potassium titanate fiber, carbon fiber, carbon nanotubes, carbon hollow spheres, fullerenes, anthracite powder, cellulose nanofibers, artificial cryolite (cryolite), titanium oxide, magnesium oxide, basic magnesium carbonate, dolomite, calcium sulfite, mica, asbestos, calcium silicate, molybdenum sulfide, boron fiber, silicon carbide fiber, etc. Considering the hardness and the large effect of improving strength, glass-based fillers, minerals, and carbon fibers are preferred. Considering the narrow particle size distribution and fiber diameter distribution, glass-based fillers are further preferred. These inorganic reinforcing materials can be used alone or in combination of two or more.

[0062] Examples of the glass-based filler preferably used in the present invention include glass fibers, glass beads, glass flakes, and foamed glass beads.

[0063] In the scope of not damaging the effect of the present invention, in order to improve the adhesion of inorganic reinforcement and polymer particles, it is possible to use the material that inorganic reinforcement has been implemented with surface treatment.As such surface treated example, silane coupling agents such as aminosilane, epoxysilane, acrylic silane etc. can be enumerated.These surface treatment agents can be immobilized by coupled reaction on the surface of inorganic reinforcement, or cover the surface of inorganic reinforcement, but when reusing modeling with large-scale molding machine, even in order not to mix new polymer particles and polymer particle compositions in a large amount, it is also possible to maintain the surface smoothness, mechanical strength of modeling object, thereby being difficult to start from this point of modification by heat etc., preferably immobilized by coupled reaction.

[0064] The amount of the inorganic reinforcing material is preferably 10 to 200 parts by mass relative to 100 parts by mass of the polymer particles. The upper limit of the amount is preferably 150 parts by mass or less, more preferably 100 parts by mass or less, and particularly preferably 75 parts by mass or less, from the viewpoint of not deteriorating the fluidity of the polymer particles and obtaining a molded object with good surface smoothness. In addition, from the viewpoint of improving the mechanical properties of the molded object, the lower limit of the amount is more preferably 15 parts by mass or more, more preferably 20 parts by mass or more, and particularly preferably 25 parts by mass or more.

[0065] In the polymer particles (polymer particle composition) of the present invention, the flow aid and the inorganic reinforcing material may be contained in an amount within the above-mentioned preferred range, respectively.

[0066] In addition, the polymer particles (polymer particle composition) of the present invention may also contain other additives. Examples of other additives include antioxidants, heat stabilizers, weathering agents, lubricants, pigments, dyes, plasticizers, antistatic agents, flame retardants, carbon black, titanium dioxide, etc., which are used to improve the stability of the polymer particles.

[0067] The polymer particles and polymer particle compositions of the present invention are useful materials for recovering the polymer particles and polymer particle compositions that remain after a three-dimensional object is manufactured by powder bed fusion and reused for molding. Figure 1 A method for producing a three-dimensional object using the polymer particles and polymer particle composition of the present invention will be described below.

[0068] In step (a), the table 2 of the tank 1 forming the object is lowered.

[0069] In step (b), the table 4 of the tank 3 (hereinafter sometimes referred to as the supply tank) which is previously filled with the polymer particles or polymer particle composition P to be supplied to the tank 1 forming the shaped object is raised to a height just enough to supply the polymer particles or polymer particle composition P in an amount sufficient to fill the predetermined stacking height formed in the tank 1. Then, the recoater 5 is moved from the left end of the supply tank 3 in the figure to the right end of the tank 1 to stack the polymer particles or polymer particle composition P on the tank 1. In addition, the direction parallel to the movement of the recoater 5 is set as the X direction, and the direction orthogonal to the moving direction of the recoater 5 on the powder surface of the polymer particles or polymer particle composition P is set as the Y direction. Reference numeral 7 represents a coordinate system showing the X direction, the Y direction, and the Z direction. Reference numeral 8 represents the surface direction of the stacked polymer particles or polymer particle composition, and reference numeral 9 represents the height direction of the stacked polymer particles or polymer particle composition.

[0070] In step (c), the polymer particles or polymer particle composition P filled in the groove 1 in a predetermined stacking height in step (b) are provided with meltable thermal energy 6 to selectively melt and sinter them according to the modeling data.

[0071] In the powder bed fusion method, the three-dimensional object 10 is obtained by repeatedly performing the above steps (a) to (c).

[0072] In step (d), the three-dimensional object 10 in the tank 1 and the polymer particles and the polymer particle composition 11 remaining without forming the object 10 are separated and recovered.

[0073] When recycling the modeling, the polymer particles and polymer particle composition 11 recovered in step (d) are used as polymer particles or polymer particle composition P, and steps (a) to (c) are carried out again. At this time, for the polymer particles and polymer particle composition 11 that remain without forming a modeled object, new polymer particles and polymer particle compositions that have not been used for modeling can be added to carry out recycling modeling. From the viewpoint of reducing waste particles, the weight ratio of the remaining polymer particles and polymer particle compositions to the new polymer particles and polymer particle compositions is preferably 70 / 30 or more, more preferably 80 / 20 or more, further preferably 90 / 10 or more, particularly preferably 95 / 5 or more, and particularly preferably 100 / 0.

[0074] As a method of selective melting sintering in step (c), for example, a selective laser sintering method can be cited, in which polymer particles or a polymer particle composition are bonded by irradiating laser light in a shape corresponding to the cross-sectional shape of the object to be molded. In addition, a selective absorption (or inhibition) sintering method including a printing step of printing an energy absorption accelerator or an energy absorption inhibitor in a shape corresponding to the cross-sectional shape of the object to be molded and a step of bonding resin powder using electromagnetic radiation can also be cited.

[0075] As the laser used in the selective laser sintering method, there is no particular restriction as long as the quality of the polymer particles or the polymer particle composition or the molded object is not damaged. For example, carbon dioxide laser, YAG laser, excimer laser, He-Cd laser, semiconductor excitation solid laser, etc. can be listed. Among them, carbon dioxide laser is preferred because of its simple operation and easy control.

[0076] In addition, as the electromagnetic radiation used for selective absorption (inhibition) of sintering, any radiation that does not damage the quality of the polymer particles, polymer particle composition, or molded object can be used, but infrared radiation is preferred because it can obtain relatively cheap energy suitable for molding. In addition, the electromagnetic radiation may be interfering or not.

[0077] Energy absorption accelerators are substances that absorb electromagnetic radiation. Examples of such substances include carbon black, carbon fibers, copper hydroxyphosphate, near-infrared absorbing dyes, near-infrared absorbing pigments, metal nanoparticles, polythiophene, poly(p-phenylene sulfide), polyaniline, polypyrrole, polyacetylene, poly(p-phenylene vinylene), poly(p-phenylene), poly(styrene sulfonate), poly(3,4-ethylenedioxythiophene)-poly(styrene phosphonate)-p-diethylaminobenzaldehyde diphenylhydrazone, or conjugated polymers composed of these. These substances may be used alone or in combination.

[0078] Energy absorption inhibitors are substances that have difficulty absorbing electromagnetic radiation. Examples of such substances include substances that reflect electromagnetic radiation such as titanium, heat-insulating powders such as mica powder and ceramic powder, and water, and these substances can be used alone or in combination.

[0079] These selective absorbents or selective inhibitors may be used alone or in combination.

[0080] In the step of printing the selective absorber or selective inhibitor in a shape corresponding to the cross-sectional shape of the object to be formed, a known method such as inkjet can be used. In this case, the selective absorber or selective inhibitor can be used directly or dispersed or dissolved in a solvent.

[0081] The large molding machine in the present invention refers to a machine with a workpiece size of 0.01 m 3 The molding device is a molding device of the type described above. For example, RaFaEIII300 (manufactured by Aspect Co., Ltd.) and RaFaEIII550 (manufactured by Aspect Co., Ltd.) can be cited. The molding time when using these large molding machines depends on the amount of polymer particles and polymer particle compositions filled, but in order to obtain a large number of molded objects from one molding, it generally takes more than 12 hours. Therefore, the polymer particles and polymer particle compositions are exposed to a temperature slightly below the melting point for a long time and deteriorate.

[0082] The polymer particles and polymer particle compositions of the present invention are effective in that, when a large-scale molding machine with a long molding time is used for recycling molding, even if a large amount of new polymer particles and polymer particle compositions are not mixed, the surface smoothness and mechanical strength of the molded object can be maintained, and the recyclability of the residual particles is excellent. This index can be evaluated by the change rate of the surface smoothness of the three-dimensional molded object during recycling molding, the change rate of the mechanical strength of the three-dimensional molded object during recycling molding, and the recovery rate of the polymer particles or polymer particle compositions remaining after three-dimensional molding.

[0083] The rate of change in the surface smoothness of the three-dimensional object during reuse molding in the present invention can be calculated by dividing the surface roughness of the object obtained by recycling (remaining polymer particles and polymer particle compositions) and (new polymer particles and polymer particle compositions) in a weight ratio of 80 / 20 by the surface roughness of the object obtained by molding using only new polymer particles and polymer particle compositions.

[0084] The rate of change of the surface smoothness of the three-dimensional object during reuse (the rate of change of the surface roughness of the object) is preferably 0.8 or more and 1.2 or less. The closer the rate of change is to 1, the more it means that the surface smoothness can be maintained during reuse. The upper limit is more preferably 1.15 or less, and more preferably 1.1 or less. The lower limit is more preferably 0.85 or more, and more preferably 0.9 or more.

[0085] The surface roughness of the object is obtained by observing the surface of the object with an optical microscope, imaging the concavities and convexities on the surface of the object in three dimensions in an automatic synthesis mode, obtaining the height distribution of the cross section over a length of more than 1 mm, and calculating the surface roughness Ra (center line average roughness) by arithmetic averaging.

[0086] The surface roughness of the three-dimensional object of the present invention is a smooth surface of 15 μm or less due to the effect of the spherical shape of the polymer powder. The smaller the surface roughness, the higher the quality, so it is preferably 10 μm or less, and more preferably 5 μm or less. In addition, the lower limit is not particularly limited, preferably small, but the lower limit is usually 1 μm.

[0087] The rate of change in the mechanical strength of the three-dimensional shaped object during reuse molding in the present invention can be calculated by dividing the bending strength of the shaped object obtained by recycling (remaining polymer particles and polymer particle compositions) and (new polymer particles and polymer particle compositions) in a weight ratio of 80 / 20 by the bending strength of the shaped object obtained when molding using only new polymer particles and polymer particle compositions.

[0088] The change rate of the mechanical strength of the three-dimensional modeling object during the reuse modeling is preferably 0.8 or more and 1.2 or less. The closer the change rate is to 1, the more the mechanical strength can be maintained during the reuse modeling. The upper limit is more preferably 1.15 or less, and more preferably 1.1 or less. The lower limit is more preferably 0.85 or more, and more preferably 0.9 or more.

[0089] The flexural strength of the molded object is a value of the maximum flexural stress measured in accordance with Japanese Industrial Standards (JIS Standards) JIS K 7171 (2016) “Plastics - Method for Determination of Flexural Properties”.

[0090] The recovery rate of the polymer particles or polymer particle composition remaining after three-dimensional modeling is evaluated as follows. Collect 100g of polymer particles or polymer particle composition remaining after three-dimensional modeling, measure the weight of the polymer particles or polymer particle composition passing through a 500μm sieve, and calculate the weight of the polymer particles or polymer particle composition passing through the sieve relative to the added polymer. The recovery rate of the polymer particles or polymer particle composition remaining after the three-dimensional modeling of the present invention is preferably 30% by weight or more. The higher the recovery rate, the easier it is to recover the residual polymer particles. The lower limit is more preferably 40% by weight or more. The upper limit is 100% by weight.

[0091] The three-dimensional object of the present invention is photographed by X-ray CT, and the size of each independent hole observed as a void can be expressed as the diameter of an equivalent sphere. The average equivalent sphere diameter of the voids observed by X-ray CT measurement of the three-dimensional object of the present invention is characterized in that it is greater than 1 μm and less than 100 μm. In the case of melt molding that does not rely on the three-dimensional molding process, the average equivalent sphere diameter of the voids is usually designed to be less than 1 μm. In the case of intentional formation of voids such as foam molding, the average equivalent sphere diameter of the voids usually exceeds 100 μm. Therefore, the average equivalent sphere diameter is greater than 1 μm and less than 100 μm, which is a characteristic of the three-dimensional object. As described above, in three-dimensional molding under normal pressure, since a certain amount of voids are generated, the lower limit is preferably greater than 3 μm, more preferably greater than 5 μm, and further preferably greater than 10 μm. Since large voids will become defect points and become the cause of reduced strength of the object, the upper limit is preferably less than 80 μm, more preferably less than 60 μm, and further preferably less than 50 μm.

[0092] The ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide constituting the three-dimensional shaped object of the present invention is characterized by being 0.01 or more and 0.8 or less. The smaller the ratio of the terminal carboxyl group amount to the terminal amino group amount, the better the storage stability of the shaped object. The upper limit is preferably 0.8 or less, more preferably 0.6 or less, further preferably 0.4 or less, particularly preferably 0.2 or less, and particularly preferably 0.1 or less. If the ratio of the terminal carboxyl group amount to the terminal amino group amount is too small, the mechanical strength of the shaped object is reduced. The lower limit is more preferably 0.02 or more, and more preferably 0.04 or more.

[0093] The amount of terminal carboxyl groups of the polyamide constituting the three-dimensional structure is determined by dissolving the three-dimensional structure in benzyl alcohol and then neutralizing and titrating with a potassium hydroxide ethanol solution. The amount of terminal amino groups of the three-dimensional structure is determined by dissolving polymer particles in PEA (phenol-ethanol solvent) and then neutralizing and titrating with a hydrochloric acid aqueous solution.

[0094] The terminal regulating agent content of the three-dimensional object in the present invention refers to the weight percentage concentration of the terminal regulating agent contained in the polyamide constituting the three-dimensional object and remaining without reacting with the polyamide.

[0095] The terminal regulating agent content of the three-dimensional object is calculated by adding the three-dimensional object to a solvent that does not dissolve the polymer but dissolves only the terminal regulating agent, stirring the mixture, and measuring the weight of the terminal regulating agent extracted into the solvent.

[0096] In the present invention, the content of the terminal regulator in the three-dimensional object is greater than 0% by weight and less than 0.15% by weight. The higher the content of the terminal regulator, the worse the mechanical properties of the object or the coloration of the three-dimensional object, so the upper limit is more preferably less than 0.1% by weight, more preferably less than 0.07% by weight, particularly preferably less than 0.05% by weight, and particularly preferably less than 0.02% by weight. The lower limit is more than 0% by weight, but preferably more than 0.00001% by weight, and more preferably more than 0.0001% by weight.

[0097] The polymer particles of the present invention can be manufactured with reference to the following method described in the International Publication WO2022 / 181634 published by the inventors, but are not limited to the method, wherein the polyamide monomer (a) of the present application is polymerized by adding a terminal regulator (C) in the presence of a polymer (B) incompatible with the obtained polyamide, thereby obtaining polymer particles (A) composed of polyamide. However, in the method described in the International Publication WO2022 / 181634, the terminal regulator content of the polymer particles (A) exceeds 0.2% by weight. Therefore, in order to obtain the polymer particles of the present invention, it is necessary to further reduce the terminal regulator content by heating and washing the polymer particles (A).

[0098] In addition, the polymer particles of the present invention can be produced by using the following production method. If the following production method is used, the polymer particles of the present invention can be obtained without performing the above-mentioned heating and washing steps of the polymer particles for reducing the content of the terminal regulator. The production method is a method for producing polymer particles by polymerizing a polyamide monomer (a) in the presence of a polymer (B) and a terminal regulator (C), characterized in that at the beginning of polymerization, the polyamide monomer (a) is uniformly dissolved in the polymer (B), and after polymerization, polymer particles (A) are precipitated, and the solubility parameter δ of the polyamide, polymer (B), and terminal regulator (C) constituting the polymer particles (A) is A , δ B , δ C Satisfy 2≤(δ B -δ C ) 2 -(δ A -δ C ) 2 ≤50[(J / cm 3 )], the amount of the terminal regulator (C) is 0.001 mol% or more and 4.0 mol% or less.

[0099] By using such a method, polymer particles composed of polyamide of the present invention for use in manufacturing three-dimensional objects by powder bed fusion can be obtained, the sphericity of the polymer particles is greater than 80, the average particle size of the polymer particles is greater than 1 μm and less than 100 μm, the ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide constituting the polymer particles is greater than 0.01 and less than 0.8, the terminal regulator content of the polymer particles is greater than 0 weight % and less than 0.2 weight %, and polymer particles for manufacturing three-dimensional objects can be obtained.

[0100] In the present invention, the polyamide monomer (a) is polymerized to form a polyamide. Examples of such polyamide monomers include aminocaproic acid, aminoundecanoic acid, aminododecanoic acid, p-hydroxybenzoic acid, 4-aminobutyric acid and other amino acids, caprolactam or lauramide, 2-pyrrolidone and other lactams, selected from (dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, undecane dioic acid, dodecane dioic acid, terephthalic acid, isophthalic acid) and (diamines such as hexamethylenediamine, nonamethylenediamine, decanediamine, undecane diamine, dodecane diamine, 1,4-diaminobutane, pentamethylene diamine) mixtures or their salts, etc. These polyamide monomers can be used in two or more kinds within the scope of not damaging the present invention, and can also contain other copolymerizable components. From the viewpoint of obtaining a polyamide having thermal properties suitable for molding, amino acids such as aminoundecanoic acid and aminododecanoic acid, lactams such as lauramide, dicarboxylic acids selected from sebacic acid, undecanedioic acid, dodecanedioic acid, and mixtures of diamines selected from decanediamine, undecanediamine, dodecanediamine, or salts thereof are preferred.

[0101] The polymer (B) is a polymer that dissolves in the monomer (a) of the polyamide at the beginning of polymerization but is incompatible with the polyamide after polymerization. From the viewpoint of making the generated polymer particles fine and having high solubility in the monomer (a) and narrowing the particle size distribution, the polymer (B) is preferably incompatible with the polyamide but has high affinity. In other words, the affinity between the monomer (a) / polymer (B) or between the polyamides constituting the polymer (B) / polymer particles (A) is determined by setting the solubility parameter (hereinafter referred to as SP value) of each to δ a , δ B , δ A (J 1 / 2 / cm 3 / 2 ), the difference between monomer (a) and polymer (B) can be expressed as the square of the difference in their solubility parameters, i.e. (δ a- δ B ) 2 It means that the polyamide constituting the polymer (B) and the polymer particles (A) can be differentiated by the square of the difference in their solubility parameters, i.e. (δ A -δ B ) 2The closer it is to zero, the higher the affinity is, and the easier it is to dissolve or be compatible. However, due to the δ a and δ A Different from the monomer (a), the polyamide is less likely to form an aggregate. From the viewpoint of preventing the polymer (B) from being insoluble in the monomer (a) and forming an aggregate, it is preferred that (δ a -δ B ) 2 Satisfies the range of 0.1 to 25. (δ a- δ B ) 2 The lower limit of is more preferably 0.3 or more, further preferably 0.5 or more, and particularly preferably 1 or more. (δ a -δ B ) 2 The upper limit of (δ) is more preferably 16 or less, further preferably 12 or less, particularly preferably 10 or less, and most preferably 7 or less. On the other hand, in order to prevent the polymer (B) from being uniformly compatible and failing to obtain polymer particles, and from the viewpoint of preventing the polyamide from becoming agglomerates due to incompatibility, (δ A -δ B ) 2 It is preferred to satisfy the range of 0.1 to 16. A -δ B ) 2 The lower limit of is more preferably 0.3 or more, further preferably 0.5 or more, and particularly preferably 1 or more. (δ A -δ B ) 2 The upper limit of is more preferably 12 or less, further preferably 10 or less, particularly preferably 7 or less, and most preferably 4 or less.

[0102] In addition, the SP value is expressed as a value calculated based on the cohesive energy density and molar molecular volume of Hoftyzer-Van Krevelen described in Properties of Polymers 4th Edition (written by DW Van Krevelen, published by Elsevier Science in 2009), Chapter 7, page 215. When it cannot be calculated by this method, it is expressed as a value calculated based on the cohesive energy density and molar molecular volume of Fedors described on page 195 of the same chapter. In addition, when two or more polyamide monomers (a), polymers (B) or terminal regulators (C) are used, the value obtained by adding the product of the respective SP values ​​and the molar fractions is expressed.

[0103] Specific examples of the polymer (B) preferably used in the method for producing polymer particles of the present invention include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polypentamethylene glycol, polyhexamethylene glycol, polyethylene glycol-polypropylene glycol copolymers, polyethylene glycol-polytetramethylene glycol copolymers, and alkyl ethers in which the hydroxyl groups at one or both ends of these are blocked with a methyl group, ethyl group, propyl group, isopropyl group, butyl group, hexyl group, octyl group, decyl group, dodecyl group, hexadecyl group, octadecyl group, or the like, and alkyl phenyl ethers blocked with an octylphenyl group or the like. In particular, polyethylene glycol, polyethylene glycol-polypropylene glycol copolymer, polypropylene glycol, polytetramethylene glycol, and alkyl ethers thereof are preferred because of their excellent compatibility with the polyamide monomer (a) and narrow particle size distribution of the obtained polymer particles. Polyethylene glycol and polyethylene glycol-polypropylene glycol copolymer are further preferred from the viewpoint of excellent compatibility with water used as a solvent, and polyethylene glycol is most preferred. Two or more of these may be used simultaneously within the scope of not impairing the present invention.

[0104] The terminal regulator (C) is a compound that reacts with the terminal amino group or terminal carboxyl group of the polyamide during polymerization to adjust the amount of the terminal amino group or terminal carboxyl group of the polyamide. If the polymer particles with the adjusted amount of the terminal amino group or terminal carboxyl group of the polyamide are used, the increase in the molecular weight of the polyamide can be suppressed during the reuse molding in a large molding machine, and the surface smoothness and mechanical strength of the molded object can be maintained.

[0105] The terminal regulator (C) in the present invention is a compound that reacts with a terminal amino group or a terminal carboxyl group of a polyamide to adjust the amount of the terminal amino group or the amount of the terminal carboxyl group of the polyamide.

[0106] The terminal regulator is used according to the type of polyamide monomer constituting the polymer particles. When dicarboxylic acids or diamines are used as polyamide monomers, monofunctional compounds are used as terminal regulators, and when amino acids or lactams are used as polyamide monomers, in addition to monofunctional compounds, bifunctional compounds can also be used as terminal regulators.

[0107] As monofunctional terminal regulators, monoamines or monocarboxylic acids can be cited. Specific examples of monoamines include hexylamine, octylamine, dodecylamine, hexadecylamine, octadecylamine, aniline, aniline derivatives, benzylamine, phenylethylamine, etc. Specific examples of monocarboxylic acids include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, lactic acid, malic acid, citric acid, benzoic acid, benzoic acid derivatives, etc. As difunctional terminal regulators, diamines or dicarboxylic acids can be cited. Specific examples of diamines include hexamethylenediamine, nonamethylenediamine, decanediamine, undecanediamine, dodecanediamine, and phenylenediamines, and specific examples of dicarboxylic acids include adipic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, terephthalic acid, and isophthalic acid. From the viewpoint of suppressing agglomeration during particle formation, monocarboxylic acids as monofunctional terminal regulators are more preferred, and from the viewpoint of suppressing the disappearance of monocarboxylic acids even at high temperatures during polymerization, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, citric acid, benzoic acid, and benzoic acid derivatives are particularly preferred.

[0108] Furthermore, by selecting the polyamide constituting the polymer particles (A), the polymer (B), and the terminal regulator (C), the relationship between the solubility parameters satisfies 2≤(δ B -δ C ) 2 -(δ A -δ C ) 2 ≤50[(J / cm 3 )], the content of the terminal regulator contained in the polymer particles (A) can be reduced.

[0109] Here (δ A -δ C ) 2 ,(δ B -δ C ) 2 Indicates the affinity between the components. (δ A -δ C ) 2 represents the affinity between the polyamide constituting the polymer particles (A) and the terminal regulator (C), (δ B -δ C ) 2 Indicates the affinity between the polymer (B) and the terminal regulator (C). (δ A -δ C ) 2The closer to zero, the easier it is for the terminal regulator (C) to be compatible with the polyamide constituting the polymer particles (A). B -δ C ) 2 The closer it is to zero, the more compatible the terminal regulator (C) is with the polymer (B). (δ B -δ C ) 2- (δ A -δ C ) 2 The lower limit of is preferably 2 or more, more preferably 5 or more, further preferably 10 or more, and particularly preferably 15 or more. B -δ C ) 2 -(δ A -δ C ) 2 The upper limit of is preferably 45 or less, more preferably 40 or less, further preferably 35 or less, and particularly preferably 30 or less in order to suppress the aggregation of the terminal regulator (C).

[0110] The amount of the terminal regulator is preferably 0.001 mol% or more and 4.0 mol% or less relative to the total amount of the added polyamide monomers. If the amount of the added substance is greater than 4.0 mol%, the molecular weight of the polyamide cannot be increased and the mechanical strength is reduced, which is not preferred. The upper limit of the amount of the terminal regulator is more preferably 2.0 mol% or less relative to the total amount of the added polyamide monomers, and further preferably 1.0 mol% or less. If the amount of the terminal regulator is less than 0.001 mol%, in order to maintain the surface smoothness and mechanical strength of the molded object when the large-scale molding machine is used for recycling molding, it is necessary to add an excessive amount of new polymer particles and polymer particle compositions. The lower limit of the amount of the terminal regulator is more preferably 0.005 mol% or more relative to the total amount of the added polyamide monomers, and further preferably 0.01 mol% or more.

[0111] As a method for polymerizing polyamide monomers into polyamide, a known method can be used. The method depends on the type of polyamide monomer. For example, in the case of amino acids, mixtures of dicarboxylic acids and diamines or their salts, a polycondensation reaction can be used. In addition, in the case of lactams, anionic ring-opening polymerization using alkali metals such as sodium or potassium or organic metal compounds such as butyl lithium and butyl magnesium as initiators, cationic ring-opening polymerization using acids as initiators, hydrolytic ring-opening polymerization using water, etc. are generally used. From the viewpoint of drainage treatment, hydrolytic ring-opening polymerization is more preferred.

[0112] In order to make the ratio of the amount of terminal carboxyl groups to the amount of terminal amino groups of the polyamide constituting the polymer particles be 0.01 or more and 0.8 or less, in addition to the method using the above-mentioned terminal regulating agent (C), there can be mentioned a method in which, when producing the polymer particles using dicarboxylic acids and diamines as the polyamide monomers (a) in the presence of the polymer (B), dicarboxylic acids and diamines are polymerized in unequal amounts.

[0113] When dicarboxylic acids and diamines are polymerized in unequal amounts, the amount of either dicarboxylic acid or diamine is excessive. If the amount of the lesser party is subtracted from the more amount of the party as the difference, the difference is preferably 0.001 mol% or more and 4.0 mol% or less relative to the lesser party of the dicarboxylic acid or diamine. If the amount of the added substance is greater than 4.0 mol%, the polyamide cannot be made high molecular weight, and the mechanical strength is reduced, so it is not preferred. The upper limit of the difference is more preferably less than 2.0 mol%, and more preferably less than 1.0 mol%. If the difference is less than 0.001 mol%, in order to maintain the surface smoothness and mechanical strength of the molded object when the mold is reused in a large molding machine, it is necessary to add an excess of new polymer particles and polymer particle compositions. The lower limit of the difference is more preferably 0.005 mol% or more, and more preferably 0.01 mol% or more.

[0114] Furthermore, polymerization is preferably performed in the presence of an excess of dicarboxylic acid from the viewpoint of suppressing agglomeration during particle formation and from the viewpoint that the terminal amino groups of the polyamide constituting the polymer particles are more susceptible to oxidation than the terminal carboxyl groups.

[0115] In the manufacture method of polymer particles, within the scope of not damaging the effect of the present invention, a polymerization accelerator may also be added. As an accelerator, a known accelerator may be used, for example, inorganic phosphorus compounds such as phosphoric acid, phosphorous acid, hypophosphorous acid, pyrophosphoric acid, polyphosphoric acid, boric acid and their alkali metal salts, alkaline earth metal salts may be cited. These may also use more than two kinds. As an addition amount, it may be appropriately selected, but preferably less than 1 mass part is added relative to 100 mass parts of polyamide monomers.

[0116] In order to separate the polymer particles from the mixture of the polymer particles after the polymerization is completed and the polymer incompatible with the obtained polyamide, the method of separating the mixture after the polymerization is completed by spraying it into a poor solvent for the polymer particles, or separating the method after adding a poor solvent for the polymer particles in the reaction tank, etc. can be cited. From the viewpoint of preventing the polymer particles from melting and combining with each other and increasing the particle size distribution index, it is preferred to cool the mixture below the melting point of the polymer particles, more preferably below the crystallization temperature, and then spray the mixture into a poor solvent for the polymer particles to separate the method, or add a poor solvent for the polymer particles to the reaction tank to separate the method, etc., more preferably, add a poor solvent for the polymer particles in the reaction tank to separate the method. As a separation method, known methods such as decompression, pressure filtration, decantation, centrifugal separation, and spray drying can be appropriately selected.

[0117] As a poor solvent for polymer particles, preferably a solvent that does not dissolve the polymer but can dissolve the polyamide monomer and the polymer incompatible with the obtained polyamide. Such a solvent can be appropriately selected, and alcohols such as methanol, ethanol, isopropanol or water can be listed. From the viewpoint of preventing the formation of voids in the molded object caused by the organic solvent, water is preferred.

[0118] The cleaning, separation and drying of the polymer particles can be implemented by known methods. As a cleaning method for removing attachments or inclusions on the polymer particles, redispersion cleaning can be used, or heating can be appropriately applied. As a solvent used in cleaning, there is no restriction as long as it is a solvent that does not dissolve the polymer particles but can dissolve the polyamide monomer and the polymer incompatible with the obtained polyamide. From the economic point of view, water is preferred. For separation, decompression, pressure filtration, decantation, centrifugation, spray drying, etc. can be appropriately selected. Through this washing and separation, the polymer incompatible with the obtained polyamide is removed to a degree of less than 0.001% by mass relative to the polymer particles. Drying is preferably implemented below the melting point of the polymer particles, or decompression can be applied. Air drying, hot air drying, heating drying, reduced pressure drying or freeze drying can be selected.

[0119] As a method for heating and washing the obtained polymer particles (A) to reduce the content of the terminal regulating agent, there are a method of heating the polymer particles (A) at a temperature of -5°C from the melting point in a nitrogen atmosphere until the content of the terminal regulating agent is 0.2 wt% or less, a method of redispersing and washing with a solvent that does not dissolve the polymer particles (A) but dissolves the terminal regulating agent (C), and a method of washing the polymer particles (A) with a solvent that does not dissolve the polymer particles (A) but dissolves the terminal regulating agent (C).

[0120] Example

[0121] The present invention will be described below based on examples, but the present invention is not limited thereto.

[0122] (1) Sphericity of polymer particles

[0123] Thirty particles were randomly observed from a scanning electron microscope (JSM-6301NF, manufactured by JEOL Ltd.), and the sphericity of the polymer particles was calculated from the short axis and the long axis according to the following formula.

[0124]

[0125] In the above formula, S represents sphericity, a represents the major axis, b represents the minor axis, and n represents the number of measurements, which is 30.

[0126] (2) Average particle size

[0127] In the laser diffraction particle size distribution measuring device (microtrac MT3300EXII) manufactured by Nikkiso Co., Ltd., about 100 mg of polymer particles and polymer particle compositions are added in advance until the concentration of the dispersion dispersed with about 5 mL of deionized water can be measured. After ultrasonic dispersion is performed at 30 W for 60 seconds in the measuring device, the average particle size is measured based on the particle size distribution measured at a measuring time of 10 seconds. The average particle size refers to the D50 particle size, which refers to the particle size when the cumulative distribution from the small particle size side reaches 50%. In addition, the refractive index used during the measurement is 1.52, and the refractive index of the medium (deionized water) is 1.333.

[0128] (3) Content of polyamide constituting polymer particles, polymer particle composition, or three-dimensional shaped object

[0129] The content of polyamide constituting polymer particles, polymer particle compositions and three-dimensional shaped objects is measured using an automatic differential thermal and thermogravimetric simultaneous measuring apparatus DTG-60 manufactured by Shimadzu Corporation. In a nitrogen atmosphere, 10 mg of polymer particles, polymer particle compositions and three-dimensional shaped objects are heated from 30°C to 500°C at a rate of 10°C / min and the weight reduction is measured.

[0130] (4) Quantification of terminal carboxyl groups of polyamide constituting polymer particles, polymer particle compositions, or three-dimensional structures

[0131] 0.5 g of polymer particles or polymer particle composition or three-dimensional structure was dissolved in 20 mL of benzyl alcohol and heated at 190° C. for 2 hours. After confirming the dissolution, a few drops of phenolphthalein indicator were added and titrated with 1 / 50 N-KOH ethanol solution. The point colored red was regarded as the end point and the result was obtained by the following formula.

[0132]

[0133] In the above formula, COOH is the terminal carboxyl group amount of the polyamide constituting the polymer particles, T is the titration amount of 1 / 50 N-KOH ethanol solution (mL), B is the titration amount of 1 / 50 N-KOH ethanol solution required for the blank (mL), f is the potency of 1 / 50 N-KOH ethanol solution (potency), W is the sample collection weight (g), C A It is the content (weight %) of the polyamide constituting the polymer particles or polymer particle composition, or the three-dimensional modeled object.

[0134] (5) Quantification of terminal amino groups of polyamide constituting polymer particles or polymer particle compositions or three-dimensional structures

[0135] Dissolve 0.5 g of polymer particles or polymer particle combination or three-dimensional structure in 25 ml of PEA (phenol-ethanol solvent). After confirming the dissolution, add a few drops of thymol blue indicator and titrate with 1 / 50 N-HCl aqueous solution. The point where it turns light red is the end point and the following formula is used to calculate the concentration.

[0136]

[0137] In addition, in the above formula, NH 2 represents the amount of terminal amino groups of the polyamide constituting the polymer particles, A represents the titration amount of 1 / 50 N-HCl aqueous solution (mL), B represents the titration amount of 1 / 50 N-HCl aqueous solution required for blank (mL), f represents the potency of 1 / 50 N-HCl aqueous solution, W represents the sample collection weight (g), C A It indicates the content (weight %) of the polyamide constituting the polymer particles or the polymer particle composition or the three-dimensional modeled object.

[0138] (6) The content of terminal regulator in polymer particles, polymer particle compositions or three-dimensional structures (C T )

[0139] To 10 g of a solvent that does not dissolve polymer particles but only dissolves the terminal regulator, polymer particles, a polymer particle composition, or a three-dimensional object are added so that the weight of the polyamide constituting them is 10 g, and the mixture is stirred. The weight of the terminal regulator extracted into the solvent is measured and calculated by the following formula:

[0140]

[0141] It should be noted that in the above formula, W T represents the weight of the terminal regulator extracted into the solvent, W represents the weight of the added polymer particles, polymer particle composition, or three-dimensional object, and C A It indicates the content of polyamide constituting polymer particles, polymer particle composition, or three-dimensional shaped object.

[0142] (7) Weight average molecular weight of the polyamide constituting the polymer particles or polymer particle composition

[0143] The weight average molecular weight of the polymer particles or the polymer particle composition is calculated by comparing with a calibration curve of polymethyl methacrylate using gel permeation chromatography. About 3 mg of the polymer particles are dissolved in about 3 g of hexafluoroisopropanol to prepare a measurement sample.

[0144] Device: Waters e-Alliance GPC system

[0145] Chromatographic column: HFIP-806M manufactured by Showa Denko K.K. × 2

[0146] Mobile phase: 5mmol / L sodium trifluoroacetate / hexafluoroisopropanol

[0147] Flow rate: 1.0ml / min

[0148] Temperature: 30℃

[0149] Detection: Differential refractometer

[0150] (8) Molecular weight change rate of the polyamide constituting the polymer particles or polymer particle composition before and after heating

[0151] 5 g of polymer particles or polymer particle compositions were heated for 12 hours under a nitrogen atmosphere at a temperature of -5°C, the melting point of the polyamide constituting the polymer particles or polymer particle compositions. The value obtained by dividing the weight average molecular weight of the polyamide constituting the polymer particles or polymer particle compositions after heating by the weight average molecular weight of the polyamide constituting the polymer particles or polymer particle compositions before heating was taken as the molecular weight change rate.

[0152] (9) BET specific surface area of ​​polymer particles or polymer particle composition

[0153] According to the Japanese Industrial Standard (JIS standard) JIS R1626 (1996) "Method for determining specific surface area by gas adsorption BET method", about 0.2 g of polymer particles were placed in a glass chamber using BELSORP-max manufactured by Bell Japan, and degassed at 80°C for about 5 hours, and then the krypton gas adsorption isotherm at liquid nitrogen temperature was measured and calculated by the BET method. When measuring the polymer particle composition, the flow aid and inorganic reinforcing material were removed by using the difference in specific gravity, etc.

[0154] (10) Method for measuring the melting point of polyamide constituting polymer particles or polymer particle composition

[0155] Using a differential scanning calorimeter (DSCQ20) manufactured by TA Instruments, the peak value of the endothermic peak observed when heating from 30°C at a rate of 20°C / min in a nitrogen atmosphere to a temperature 30°C higher than the end point of the melting peak was taken as the melting point.

[0156] (11) Surface roughness of three-dimensional objects

[0157] The surface roughness of the three-dimensional object was measured by using a powder bed fusion 3D printer (RaFaEIII300) manufactured by Aspect Co., Ltd., an optical microscope (VHX-5000) manufactured by Keyence Co., Ltd., and an objective lens VH-ZST (ZS-20) to observe the surface of the object at a magnification of 200 times. At this time, the software (system version 1.04) attached to the device was used to three-dimensionally image the concavities and convexities on the surface of the object in the automatic synthesis mode, and the height distribution of the cross section over a length of more than 1 mm was obtained, and the surface roughness Ra was calculated by arithmetic average.

[0158] (12) Average equivalent spherical diameter of pores in three-dimensional objects

[0159] The average equivalent spherical diameter of the pores was calculated by observing a three-dimensional transmission image of a three-dimensional object using an X-ray CT device (Xradia510Versa) manufactured by ZEISS. The measurement was performed with a resolution of 5 μm, a field of view of 5 mm, a voltage of 80 kV, and a power of 7 W. The pores in the obtained observation image were marked, and the diameter of each independent pore when it was converted into a sphere, i.e., the equivalent spherical diameter, was calculated, and the average value was obtained as the average equivalent spherical diameter of the pores.

[0160] (13) Change rate of surface smoothness of three-dimensional objects during reuse

[0161] The polymer particles or polymer particle compositions remaining after three-dimensional modeling are mixed with new polymer particles or polymer particle compositions in a weight ratio of 80 / 20. Then, the mixture is used as a raw material, and a test piece of width 10mm, length 80mm, and thickness 4mm is made using a powder bed fusion method 3D printer (RaFaEIII300) made by Aspect Co., Ltd., with a length direction of 80mm as the X direction during production. The surface roughness of the test piece obtained when the mixed product is used for modeling is divided by the surface roughness of the test piece obtained when only new polymer particles or polymer particle compositions are used for modeling, thus calculating the rate of change of surface smoothness, and evaluating the rate of change with the following benchmarks.

[0162] A: 0.9 or more and 1.1 or less

[0163] B: 0.8 or more and less than 0.9, or greater than 1.1 and less than 1.2

[0164] C: less than 0.8, or greater than 1.2

[0165] (14) Determination of bending strength of shaped objects

[0166] The bending strength of the three-dimensional object is determined by using a powder bed fusion 3D printer (RaFaEIII300) manufactured by Aspect Co., Ltd. to make a test piece with a width of 10 mm, a length of 80 mm, and a thickness of 4 mm. During the production, the length direction of 80 mm is the X direction. Then, the bending strength of the test piece in the X direction is measured using a Tensilon universal testing machine (TENSIRON TRG-1250) manufactured by A&D Dei Co., Ltd. In addition, according to JIS K7171 (2016), a three-point bending test is performed under the conditions of a distance between support points of 64 mm and a test speed of 2 mm / min, and the maximum bending stress measured is taken as the bending strength. The measurement temperature is room temperature (23°C), the number of measurements is n=5, and their average value is calculated.

[0167] (15) Change rate of mechanical strength of three-dimensional objects during reuse

[0168] The polymer particles or polymer particle compositions remaining after three-dimensional modeling are mixed with new polymer particles or polymer particle compositions at a weight ratio of 80 / 20. Then, the mixture is used as a raw material, and a test piece of 10 mm in width, 80 mm in length, and 4 mm in thickness is made using a powder bed fusion method 3D printer (RaFaEIII300) made by Aspect Co., Ltd., with a length direction of 80 mm as the X direction during production. By dividing the bending strength of the test piece obtained when using the mixture modeling by the bending strength of the test piece obtained when only new polymer particles and polymer particle compositions are used to model, the rate of change of mechanical strength is calculated, and the rate of change is evaluated with the following benchmarks.

[0169] A: 0.9 or more and 1.1 or less

[0170] B: 0.8 or more and less than 0.9, or greater than 1.1 and less than 1.2

[0171] C: less than 0.8, or greater than 1.2

[0172] (16) Recovery rate of polymer particles or polymer particle composition remaining after three-dimensional modeling

[0173] Collect 100 g of polymer particles or polymer particle compositions remaining after three-dimensional modeling, measure the weight of the polymer particles or polymer particle compositions passing through a 500 μm sieve, and take the ratio of the weight of the polymer particles or polymer particle compositions passing through the sieve to the weight of the polymer particles or polymer particle compositions added as the recovery rate.

[0174] The evaluation was performed according to the following criteria.

[0175] A: The recovery rate is 40% by weight or more.

[0176] B: The recovery rate is 30% by weight or more and less than 40% by weight.

[0177] C: The recovery rate is less than 30% by weight.

[0178] A~B are qualified, and C is unqualified.

[0179] [Production Example 1]

[0180] In a 9L autoclave, 600g of aminododecanoic acid (manufactured by Wako Pure Chemical Industries, Ltd.) as a polyamide monomer, 2400g of polyethylene glycol (first-grade polyethylene glycol 20000 manufactured by Wako Pure Chemical Industries, Ltd.) as a polymer incompatible with the obtained polyamide, 4.2g of IRGANOX 1098 (manufactured by BASF Japan Co., Ltd.) as an antioxidant, 1500g of deionized water, and 2.7g (0.8mol%) of benzoic acid as a terminal regulator were added, sealed, heated to 1MPa with nitrogen, and then the pressure was released to 0.1MPa. The pressure-increasing and depressurizing steps were repeated three times, and after replacing the inside of the container with nitrogen, the pressure was adjusted to 0.1MPa and the container was sealed. Then, the stirring speed was set to 30rpm, and the temperature was raised to 220°C. At this time, the pressure in the system was 1.0MPa. Next, the pressure was released at a rate of 0.02 MPa / min until the internal pressure became 0 MPa. Then, nitrogen was circulated at a rate of 5 mL / min at a polymerization temperature of 220°C, and polymerization was carried out for 3 hours. Finally, it was discharged into a 2000 g water bath to obtain a slurry. After the slurry was fully homogenized by stirring, it was filtered, 2000 g of water was added to the filtrate, and it was washed at 80°C. Then, the slurry after passing through a 100 μm sieve to remove the agglomerates was filtered again, and the separated filtrate was dried at 80°C for 12 hours to obtain 480 g (yield 80%) of polymer particles. Then, it was heated for 12 hours at -5°C, the melting point of the polyamide constituting the polymer particles, in a nitrogen atmosphere. The properties of the obtained polymer particles are shown in Table 1.

[0181] [Production Example 2]

[0182] Polymer particles were obtained in the same manner as in Production Example 1 except that the terminal modifier was changed to 3.6 g of adipic acid (0.8 mol %). The properties of the obtained polymer particles are shown in Table 1.

[0183] [Production Example 3]

[0184] Polymer particles were obtained in the same manner as in Preparation Example 1 except that the polyamide monomer was changed to 900 g of 11-aminoundecanoic acid (manufactured by Sigma Aldrich), the polymer incompatible with the obtained polyamide was changed to 900 g of polyethylene glycol (first grade polyethylene glycol 20000 manufactured by Wako Pure Chemical Industries, Ltd.), the antioxidant was changed to 6.0 g of IRGANOX 1098 (manufactured by BASF Japan Ltd.), the deionized water was changed to 2700 g, and the terminal regulator was changed to 3.0 g (0.5 mol%) of benzoic acid. The properties of the obtained polymer particles are shown in Table 1.

[0185] [Production Example 4]

[0186] Polymer particles were obtained in the same manner as in Production Example 1 except that the polyamide monomer was changed to 309 g of 1,10-diaminodecane (manufactured by Tokyo Chemical Industry Co., Ltd.) and 411 g of dodecanedioic acid (manufactured by Wako Pure Chemical Industries, Ltd.), the polymer incompatible with the obtained polyamide was changed to 1080 g of polyethylene glycol (first grade polyethylene glycol 20000 manufactured by Wako Pure Chemical Industries, Ltd.), the antioxidant was changed to 5.0 g of IRGANOX 1098 (manufactured by BASF Japan Ltd.), the deionized water was changed to 900 g, and the terminal regulator was changed to 2.64 g (0.6 mol%) of benzoic acid. The properties of the obtained polymer particles are shown in Table 1.

[0187] [Production Example 5]

[0188] Polymer particles were obtained in the same manner as in Production Example 4 except that the terminal regulating agent was changed to 2.0 g (0.6 mol%) of stearic acid and the heat treatment at the melting point of the polyamide constituting the polymer particles at -5°C was not performed. The properties of the obtained polymer particles are shown in Table 1.

[0189] [Production Example 6]

[0190] Polymer particles were obtained in the same manner as in Production Example 5 except that the terminal modifier was changed to 2.4 g of lauric acid (1.0 mol%). The properties of the obtained polymer particles are shown in Table 1.

[0191] [Production Example 7]

[0192] Polymer particles were obtained in the same manner as in Production Example 1 except that the polyamide monomer was changed to 1080 g of ε-caprolactam (special grade reagent manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), the obtained polymer incompatible with polyamide was changed to 720 g of polyethylene glycol (grade 1 polyethylene glycol 6000 manufactured by Wako Pure Chemical Industries, Ltd., molecular weight 7700), the antioxidant was changed to 7.5 g of IRGANOX 1098 (manufactured by BASF Japan Ltd.), the deionized water was changed to 150 g, and the terminal regulator was changed to 9.33 g (0.8 mol%) of benzoic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). The properties of the obtained polymer particles are shown in Table 1.

[0193] [Production Example 8]

[0194] Polymer particles were obtained in the same manner as in Production Example 7 except that the terminal modifier was changed to 15.3 g (0.6 mol %) of stearic acid. The properties of the obtained polymer particles are shown in Table 1.

[0195] [Production Example 9]

[0196] Polymer particles were obtained in the same manner as in Production Example 1 except that the terminal regulating agent was not added. The properties of the obtained polymer particles are shown in Table 1.

[0197] [Production Example 10]

[0198] Polymer particles were obtained in the same manner as in Production Example 7 except that the heating was not performed at the melting point of the polyamide constituting the polymer particles -5°C. The properties of the obtained polymer particles are shown in Table 1.

[0199] [Production Example 11]

[0200] 6 kg of polymer particles obtained by repeating manufacturing example 1 were added to a 9L autoclave, sealed, pressurized to 1 MPa with nitrogen, and then released to 0.1 MPa. The steps of pressurization and release were repeated 3 times. After replacing the inside of the container with nitrogen, the pressure was adjusted to 0.1 MPa and the container was sealed. Then, the stirring speed was set to 30 rpm, the temperature was raised to 220°C, maintained for 30 minutes, and then sprayed into a 6000 g water bath. The obtained resin was chopped, and the obtained particles were cooled to -192°C with liquid nitrogen, and crushed with a turbo mill for 60 minutes to obtain polymer particles. The properties of the obtained polymer particles are shown in Table 1.

[0201] [Reference Production Example 1]

[0202] Polymer particles were obtained in the same manner as in Production Example 6 except that the terminal modifier was changed to 4.1 g (0.5 mol %) of dodecanedioic acid. The properties of the obtained polymer particles are shown in Table 1.

[0203] [Example 1]

[0204] Using 7.5 kg of polymer particles obtained by repeating the manufacturing example 1, a three-dimensional object was produced using a powder bed fusion apparatus (RaFaEIII300) manufactured by Aspect Co., Ltd. Then, 1.5 kg of new polymer particles were added to 6 kg of residual polymer particles that did not become a modeled object, and the mixture was used again to reuse the three-dimensional modeled object using a powder bed fusion apparatus (RaFaEIII300) manufactured by Aspect Co., Ltd. The properties of the three-dimensional modeled object are shown in Table 2.

[0205] [Example 2]

[0206] 7.5 g of trimethyl silylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) as a flow aid was added to 7.5 kg of polymer particles obtained by repeating Manufacturing Example 1 as a polymer particle composition, and a three-dimensional molded object was produced using a powder bed fusion device (RaFaEIII300) manufactured by Aspect Co., Ltd. Then, 1.5 kg of a new polymer particle composition was added to 6 kg of the residual polymer particle composition that did not become a molded object, and the mixture was used again using a powder bed fusion device (RaFaEIII300) manufactured by Aspect Co., Ltd. to recycle the three-dimensional molded object. The properties of the three-dimensional molded object are shown in Table 2.

[0207] [Example 3]

[0208] A molded object was prepared in the same manner as in Example 2 except that 22.5 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) and 2.25 kg of glass fiber (EGB70M-01N manufactured by Nippon Electric Glass Co., Ltd.) were added as a flow aid to 5.25 kg of the polymer particles obtained by repeatedly carrying out Production Example 1 to form a polymer particle composition. The properties of the three-dimensional molded object are shown in Table 2.

[0209] [Example 4]

[0210] A molded object was prepared in the same manner as in Example 2 except that 7.5 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) and 2.25 kg of glass beads GB731A (manufactured by Potassium Ballotini Co., Ltd., average major axis diameter 27 μm, average minor axis diameter 26 μm) were added as a flow aid to 5.25 kg of the polymer particles obtained in Production Example 1 to form a polymer particle composition. The properties of the three-dimensional molded object are shown in Table 2.

[0211] [Example 5]

[0212] A molded object was produced in the same manner as in Example 3 except that the polymer particles were changed to the polymer particles obtained in Production Example 2. Table 2 shows the properties of the three-dimensional molded object.

[0213] [Example 6]

[0214] A molded object was produced in the same manner as in Example 3 except that the polymer particles were changed to the polymer particles obtained in Production Example 3. Table 2 shows the properties of the three-dimensional molded object.

[0215] [Example 7]

[0216] A molded object was produced in the same manner as in Example 3 except that the polymer particles were changed to the polymer particles obtained in Production Example 4. Table 2 shows the properties of the three-dimensional molded object.

[0217] [Example 8]

[0218] A molded object was produced in the same manner as in Example 3 except that the polymer particles were changed to the polymer particles obtained in Production Example 5. Table 2 shows the properties of the three-dimensional molded object.

[0219] [Example 9]

[0220] A molded object was produced in the same manner as in Example 3 except that the polymer particles were changed to the polymer particles obtained in Production Example 6. Table 2 shows the properties of the three-dimensional molded object.

[0221] [Example 10]

[0222] A molded object was produced in the same manner as in Example 3 except that the polymer particles were changed to the polymer particles obtained in Production Example 7. Table 2 shows the properties of the three-dimensional molded object.

[0223] [Example 11]

[0224] A molded object was produced in the same manner as in Example 3 except that the polymer particles were changed to the polymer particles obtained in Production Example 8. Table 2 shows the properties of the three-dimensional molded object.

[0225] [Comparative Example 1]

[0226] A molded object was produced in the same manner as in Example 3 except that the polymer particles were changed to the polymer particles obtained in Production Example 9. Table 2 shows the properties of the three-dimensional molded object.

[0227] [Comparative Example 2]

[0228] A molded object was produced in the same manner as in Example 3 except that the polymer particles were changed to the polymer particles obtained in Production Example 10. Table 2 shows the properties of the three-dimensional molded object.

[0229] [Comparative Example 3]

[0230] A molded object was produced in the same manner as in Example 3 except that the polymer particles were changed to the polymer particles obtained in Production Example 11. Table 2 shows the properties of the three-dimensional molded object.

[0231] [Reference Example 1]

[0232] A molded object was produced in the same manner as in Example 3 except that the polymer particles were changed to the polymer particles obtained in Reference Production Example 1. Table 2 shows the properties of the three-dimensional molded object.

[0233]

[0234]

[0235] Industrial Availability

[0236] The polymer particles and polymer particle compositions of the present invention have high sphericity, a small ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide constituting the particles, and a small amount of impurities. Therefore, when the polymer particles and polymer particle compositions are recycled in a large-scale molding machine, the surface smoothness and mechanical strength of the molded object can be maintained even without mixing a large amount of new polymer particles and polymer particle compositions, and the residual particles have excellent recyclability, thereby reducing waste particles.

[0237] Description of Reference Numerals

[0238] 1 Groove for forming a sculpture

[0239] 2. The tabletop that forms the groove for the modeling object

[0240] 3. A supply tank pre-filled with polymer particles or a polymer particle composition to be supplied

[0241] 4. A table with a tank pre-filled with polymer particles or a polymer particle composition to be supplied

[0242] 5Re-applicator

[0243] 6. Heat

[0244] 7X, Y, Z coordinate system

[0245] 8. Surface direction of laminated polymer particles or polymer particle composition

[0246] 9. Height direction of stacked polymer particles or polymer particle composition

[0247] 10 Three-dimensional objects

[0248] 11. Polymer particles or polymer particle composition remaining without forming a molded object

[0249] P polymer particles or polymer particle composition

Claims

1. A polymer particle for manufacturing a three-dimensional object, which is a polymer particle composed of polyamide for manufacturing a three-dimensional object by a powder bed fusion method, the sphericity of the polymer particles is greater than 80, the average particle size of the polymer particles is greater than 1 μm and less than 100 μm, the ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide constituting the polymer particles is greater than 0.01 and less than 0.8, and the content of the terminal regulator in the polymer particles is greater than 0 weight % and less than 0.2 weight %.

2. The polymer particles for producing three-dimensional objects as described in claim 1, wherein when the polymer particles are heated at a temperature of -5°C, the melting point of the polyamide constituting the polymer particles, for 12 hours in a nitrogen atmosphere, the molecular weight change rate of the polyamide constituting the polymer particles before and after heating is greater than 0.7 and less than 1.

4. 3 . The polymer particles for producing three-dimensional objects according to claim 1 , wherein the weight average molecular weight of the polyamide constituting the polymer particles is greater than or equal to 1000 g / mol and less than or equal to 100000 g / mol.

4. The polymer particles for producing three-dimensional objects according to claim 1, wherein the amount of terminal amino groups of the polyamide constituting the polymer particles is 0.1×10 -5 mol / g or more and 4.0×10 -5 mol / g or less.

5. The polymer particles for manufacturing three-dimensional objects according to claim 1, wherein the BET specific surface area of ​​the polymer particles is 0.05 m 2 / g or more and 1m 2 / g or less.

6. The polymer particles for manufacturing three-dimensional objects according to claim 1, wherein the polyamide constituting the polymer particles comprises at least one polyamide selected from polyamide 12, polyamide 11, polyamide 1012, polyamide 1010, polyamide 6, polyamide 66 and copolymers containing any of these polyamides. 7 . A polymer particle composition for producing a three-dimensional object, comprising 0.01 parts by mass or more and 5 parts by mass or less of a flow aid based on 100 parts by mass of the polymer particles according to claim 1 . 8 . A polymer particle composition for producing a three-dimensional object, comprising 10 parts by mass or more and 200 parts by mass or less of an inorganic reinforcing material per 100 parts by mass of the polymer particle according to claim 1 . 9 . A method for producing a three-dimensional object, comprising producing the three-dimensional object by a powder bed fusion method using the polymer particles according to claim 1 .

10. A method for producing a three-dimensional object, comprising using the polymer particle composition according to claim 7 to produce the three-dimensional object by a powder bed fusion method.

11. A method for producing a three-dimensional object, comprising using the polymer particle composition according to claim 8 to produce the three-dimensional object by a powder bed fusion method.

12. A three-dimensional object obtained by powder bed fusion using polymer particles or a polymer particle composition, characterized in that: The three-dimensional molded object contains a surface with a surface roughness of less than 15 μm, the average equivalent spherical diameter of the pores observed by X-ray CT measurement is greater than 1 μm and less than 100 μm, the ratio of the terminal carboxyl group amount to the terminal amino group amount of the polyamide constituting the three-dimensional molded object is greater than 0.01 and less than 0.8, and the terminal regulator content is greater than 0 weight % and less than 0.15 weight %.

13. The method for producing polymer particles for producing three-dimensional objects according to claim 1, which is a method for producing polymer particles by polymerizing a polyamide monomer a in the presence of a polymer B and a terminal regulator C, wherein: At the beginning of polymerization, the monomer a of polyamide is uniformly dissolved in the polymer B. After polymerization, polymer particles A are precipitated. The solubility parameter δ of the polyamide, polymer B, and terminal regulator C constituting the polymer particles A is A , δ B , δ C Satisfy 2≤(δ B -δ C ) 2 -(δ A -δ C ) 2 ≤50[(J / cm 3 )], the amount of the terminal regulator C is 0.001 mol% or more and 4.0 mol% or less.

Citation Information

Patent Citations

  • Sintering powder for selective laser-sintering, method for producing the same, method for producing formed product and formed product

    JP2004137465A

  • Polyamide powder for selective sintering methods

    JP2018059093A

  • Method for manufacturing three-dimensionally shaped article using resin granular material, three-dimensionally shaped article, and resin granular material

    WO2022181634A1